Clinical and Pathogenic Characteristics of Lower Respiratory Tract Infection Treated at the Vietnam National Children's Hospital. (11th March 2020) - Pham, Hien T.; Nguyen, Phuc T. T.; Tran, Sinh T.; Phung, Thuy T. B.
Abstract : Lower respiratory tract infections are commonly caused by viruses and cause significant morbidity and mortality among children. Early identification of the pathological agent causing these infections is essential to avoid unnecessary antibiotic use and improve patient management. Multiplex PCR techniques were recently developed to detect multiple viral pathogens using a single PCR reaction. In this study, we identify viral pathogens in children with respiratory infections. We collected 194 nasopharyngeal aspirates from infants (2–24 months old) with lower respiratory tract infections treated at the Vietnam National Children's Hospital between November 2014 and June 2015 and assessed the presence of 16 virus types and subtypes by multiplex PCR using the xTAG Respiratory Viral Panel (RVP) assay. Overall, 73.7% of the samples were positive for at least one virus, and 24.2% corresponded to infections with multiple viruses. The most common viruses were respiratory syncytial virus and enterovirus/rhinovirus. These viruses were more frequent among younger patients (2–5 months old) and caused symptoms similar to those of bronchiolitis and pneumonia. The most common clinical manifestation caused by respiratory tract infection was bronchiolitis. Elevated neutrophils levels were associated with adenovirus infection. Our results showed that the xTAG Respiratory Viral Panel (RVP) can effectively detect multiple viruses causing respiratory infections in children and that the nasopharyngeal aspirates are a good sample choice to detect respiratory viruses in children. Applying this approach in the clinical setting would improve patient management and allow early diagnosis, thus avoiding the unnecessary use of antibiotics.